Female Victims of Sexual Violence, their Right to Reparation in the Transition Process of the Justice and Peace Act at the El Placer Police Station, Department of Putumayo, 2010-2015 - Calderón Robledo, Lady Andrea (DIXI, 2018)
Purpose: This article shows how female victims of sexual violence in the context of the armed conflict are still waiting to be repaired, despite the provisions in the Colombian regulations, which, since the Justice and Peace Act, have promoted a reparation scheme that remains fragile, weakening the response of the Colombian State regarding the protection of human rights. Methods: For this purpose, the research was conducted at the El Placer Police Station, jurisdiction of the municipality of Valle del Guamuez, in the department of Putumayo, through a mixed—qualitative- quantitative—method along with a type of case study, using a focused sample that allowed surveying victims and officials at the Police Station. Results: It was established that the victims in the criminal process would have three guarantees: theright to the truth, the right to justice, and the right to no impunity. Conclusions: It was concluded that, at the El Placer Police Station, women who have been victims of sexual violence have not been repaired, that the transition between the Justice and Peace Act and transitional justice has not produced results in the matter, and that the invisibility of victims continues.